TEACHERS' PERSPECTIVE OF ICT INTEGRATION ON ELT - Melfilia Nurhidayanti Savitri; Pratnyawati Nuridi Suwarso (ENGLISH, 2023)
In the 21st century, technology has become the most powerful development in the world. In the last two decades, digital usage has influenced every aspect such as economic, social, political, and education fields. Along with developments that occur every day, in the realm of education, the curriculum has changed in recent years where K13 prioritizes the use of ICT in schools. This study conducted a descriptive qualitative research design that proposed to know teachers' perspective of ICT integration on ELT, specifically about the transition during online to offline class, teacher preparation of using ICT, the effectiveness of using ICT in the class, the obstacle faced when using ICT, students achievement, the use of ICT compared with conventional media, and teachers' interest on ICT. The participants were two English teachers of SMPN 1 Singosari who have applied teaching with ICT and conventional, and using in-depth interview to collect the data. The result revealed that the teachers have interest in studying ICT but still using conventional media. It implied that there was something that needed to be fixed to maximize the use of ICT in the classroom. Furthermore, it is recommended that socialization and training sessions are frequently held to upgrade the expertise and skills in teaching English.